Acute lymphoblastic leukemia with Fusarium solani infection: a case report - Bo Liang; Tu Ni; Wenbin Ni; Xu Zhang; Qinqin Ai (Frontiers in Medicine)
BackgroundFusarium infections are rare but life-threatening in immunocompromised patients, particularly those with acute lymphoblastic leukemia (ALL) undergoing chemotherapy. This case report describes a patient with ALL who developed multifocal cutaneous Fusarium solani infections following VDCLP chemotherapy, highlighting the challenges in diagnosis and management.Case presentationA 27-year-old male ALL patient developed cutaneous infections on the right calf, left upper arm, and buttock during chemotherapy. Initial lesions presented as a 1.0 × 1.0 cm dark purple nodule on the right calf, progressing rapidly to black eschar, ulceration, and multiple metastatic lesions. Fusarium solani was confirmed via microbiological culture and molecular testing. Treatment included systemic voriconazole, local debridement, topical liposomal amphotericin B, G-CSF for neutrophil recovery, and psychological intervention for anxiety. The infections were effectively controlled with gradual wound healing, and no recurrence was observed during 2 months of follow-up.ConclusionUnusual skin lesions in immunocompromised patients, especially those with hematological malignancies receiving chemotherapy, warrant high suspicion for Fusarium infection. Timely microbiological diagnosis and early initiation of combined systemic-topical antifungal therapy, alongside neutrophil support and multidisciplinary care, are critical for improving outcomes.